An Optimal Scheduling for Medical Equipment Preventive Maintenance Over a Finite Planning Horizon Using Ant Colony Algorithm. Issue 3 (July 2017) - Saleh, Neven; Rosati, Samanta; Sharawi, Amr; Wahed, Manal Abdel; Balestra, Gabriella
Abstract : The importance of preventive maintenance management has been gradually recognized specially with the great attention to the role of health technology management. Finding the optimal schedule to perform preventive maintenance for medical equipment is rarely considered in the literature. This research suggests using ant colony optimization method to solve the problem of finding the optimal preventive maintenance schedule. We developed 2 versions of the algorithm, both starting from a prioritized medical equipment list and differing in the heuristic function. The experimental results indicate the effectiveness of the ant colony optimization algorithm for this kind of problems.